Investors’ Perceptions of the South African National Brand - Mhlungu, Nondumiso Marcia (University of the Witwatersrand, Johannesburg, 2024)
The problem of understanding investors' perceptions of the South African national brand, shaped by historical, political, and economic dynamics, is crucial for enhancing investment attraction in emerging markets like South Africa. This study aimed to explore investors' perceptions of the national brand of South Africa, focusing on understanding how these perceptions influence investment decisions. The research aimed to understand how investors perceive the South African National Brand and its impact on their investment decisions. The research problem addressed the gap in understanding how investors perceive the South African national brand. Utilising a purposive sampling technique, 15 participants were selected based on their expertise and involvement in investment activities within South Africa. Data collection involved in-depth interviews, allowing for an exploration of participants' perceptions. The study found a diverse range of perceptions among investors regarding the South African national brand. While some participants expressed confidence in the country's potential for economic growth and investment opportunities, others highlighted concerns related to political stability, infrastructure challenges, and socio-economic disparities. Despite positive attributes such as natural resources and cultural diversity, concerns about crime rates, corruption, and regulatory uncertainty were identified as significant deterrents to investment. The study concluded that while the South African National Brand possesses intrinsic strengths, addressing governance, security, and regulatory framework challenges is imperative for enhancing investor confidence and attracting sustainable investments. Based on the research findings, it is recommended that South African authorities and stakeholders engage in targeted efforts to improve and promote the national brand, emphasising its strengths and addressing areas of weakness. This could involve diplomatic efforts to enhance the country's international image, economic reforms to improve stability and attractiveness to investors, and strategic communication campaigns to showcase South Africa's potential as an investment destination. Additionally, ongoing research and monitoring of investors' perceptions should be conducted to adapt strategies effectively.
A research report submitted in fulfillment of the requirements for the Master of Management in Energy Leadership, In the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; identity; investors perception; SDG-8: Decent work and economic growth